The Impact of AI Based Decision Making, Market Intelligence, and Chatbot Integration on Business Performance in Indonesian Start-ups - Hasya, Afina; Qalid Md Sabri, Aznul (Master of Management, Faculty of Economics and Business, Diponegoro University, 2025)
With the fast-growing digital era, artificial intelligence (AI) has emerged as a principal catalyst for enhancing corporate performance, particularly for Indonesian start-ups. This study examines the effects of AI-driven decision-making, market intelligence, and chatbot implementation on Indonesian start-up business performance. Quantitative methods were employed to gather data from 250 participants, including founders, managers, and decision-makers of different start-up organizations. Structural Equation Modeling - Partial Least Squares (SEM-PLS) was employed to quantify the extent of association of independent variables with firm performance. Results indicate that all three dimensions positively and significantly influence business success, with market intelligence affecting most. Artificial intelligence supports enhanced accuracy and efficiency in decision-making, market intelligence allows organizations to comprehend consumer expectations and trends, and chatbots support increased efficiency in client communication and interaction. These results have significant implications for start-ups and governments to strategically employ AI technologies to boost competitiveness and economic growth in Indonesia.